2007
DOI: 10.1897/06-413r.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of Issoria lathonia (Lepidoptera: Nymphalidae) on zinc‐accumulating and nonaccumulating Viola species (Violaceae)

Abstract: Abstract-The larvae of Issoria lathonia L. feed in natural conditions on several Viola spp., among which are the zinc-accumulating Viola calaminaria (Gingins) Lej. and the nonmetal-accumulating Viola tricolor L. To examine how I. lathonia caterpillars cope with the naturally high foliar zinc concentration of V. calaminaria, we compared the growth of caterpillars reared on leaves varying in zinc concentration. Larvae were fed in controlled conditions with V. calaminaria and V. tricolor grown on noncontaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…However, it could be argued that the feeding of A. niobe caterpillars on zinc-accumulating V. calaminaria has negative effects on the butterfly species. A study on another fritillary species, Issoria lathonia, showed that caterpillars feeding on zinc-contaminated V. calaminaria are able to regulate their internal zinc concentration through the excretion of highly metal-concentrated faeces (Noret et al 2007). Issoria lathonia not only has the ability to cope with high heavy-metal concentrations in its host plants, but it also has its largest populations in Belgium on heavy-metal grasslands with V. calaminaria as the only host plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it could be argued that the feeding of A. niobe caterpillars on zinc-accumulating V. calaminaria has negative effects on the butterfly species. A study on another fritillary species, Issoria lathonia, showed that caterpillars feeding on zinc-contaminated V. calaminaria are able to regulate their internal zinc concentration through the excretion of highly metal-concentrated faeces (Noret et al 2007). Issoria lathonia not only has the ability to cope with high heavy-metal concentrations in its host plants, but it also has its largest populations in Belgium on heavy-metal grasslands with V. calaminaria as the only host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Boloria selene, another fritillary species of conservation concern that also feeds on V. calaminaria, regularly occurs in the heavy-metal grasslands of the study area (own observation). Additionally, the largest populations of I. lathonia in Belgium thrive in this grassland type (Noret et al 2007) and heavy-metal grasslands in southern North Rhine-Westphalia are home to strong populations of Hipparchia semele (Leopold 2006).…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Noret et al (2007) reported that leaves containing 3,800 mg Zn/kg decreased larval growth of Issoria lathonia but also documented increased leaf consumption during a larva's lifetime. Thus, a positive defensive eVect was found from the natural enemy perspective (decreased performance) yet Noret et al (2007) point out that the likely impact of Zn accumulation on plant Wtness would be negative because high Zn plants would lose more biomass to each larva that completed its development. The defensive eVect from the plant perspective is therefore listed as negative in Table 2.…”
Section: Hyperaccumulation As Elemental Plant Defense: Status Of the mentioning
confidence: 99%
“…Natural enemies native to sites that host the plant species tested were used in less than one-third of the cases (28%: 20 of the 72 cases) reported in Table 2. Using native natural enemies collected from Weld sites that host the test plant species is more rare, but has been done in some cases (e.g., Freeman et al 2007;Noret et al 2007;Wall and Boyd 2006;Hanson et al 2003;Augustyniak et al 2002;Ghaderian et al 2000;Martens and Boyd 1994).…”
Section: Hyperaccumulation As Elemental Plant Defense: Status Of the mentioning
confidence: 99%
“…Disorders in the functions of organism of insects, which inhabited an environment contaminated with zinc, such as Pterostichus oblongopunctatus, Poecilus cupreus, were observed by Bisthoven et al (1992), Martinez et al (2001Martinez et al ( , 2002Martinez et al ( , 2004, Maryanski et al (2002), Lagisz (2008). Consumption of zinc-contaminated food by insects caused delays in their development, for example, among larvae of Aglais urticae (Linnaeus, 1758) (Lindqvist, 1994), Trichoplusia ni (Hubner, 1800-1803) (Larsen et al, 1994), P. oblongopunctatus (Zygmunt et al, 2006) and Issoria lathonia (Linnaeus, 1758) (Noret et al, 2007). High concentrations of Zn led to a low survival rate of Priosotoma minuta (Nursita et al, 2005).…”
Section: Discussionmentioning
confidence: 97%